The Effect of Customer Characteristics on Service Quality in Pharmacy Retailing: An Empirical Study in the UAE - Waheed, K Abdul; Siddiqua, Ayisha (Asian Journal of Empirical Research, 2019)
The main purpose of this study was to investigate the effect of customer characteristics, especially demographic and behavioral aspects, on service quality. We investigated the effect of demographic characteristics such as gender, age, education, income, and frequency of visits. We examined the effect of behavioral characteristics such as customer loyalty and dependency. A questionnaire was developed to measure customers’ perceived service quality by reviewing current literature in this area. This study measures pharmacy service quality from the reflective model perspective. Service quality is measured on reliability, assurance, tangibility, empathy, and responsiveness. A survey was conducted among customers who visited pharmacy retail stores in Al Ain, UAE.